Investigation of microstructure and mechanical properties of austenitic steel bimetallic structures fabricated using wire arc direct energy deposition for remanufacturing applications - Rupendra Singh Tanwar; Suyog Jhavar (Journal of Advanced Joining Processes)
In this work, bimetallic structures of two austenitic steels (SS316L and SS309) were fabricated using wire arc Direct Energy Deposition (DED). The fabrication process involved in the strategy of SS316L-SS309-SS316L on an SS316L substrate sequentially. Each material deposited 10 layers to one over another and forming two interfaces. Subsequently, the microstructure and mechanical properties, were evaluated in the deposited materials and at their interface. The microstructure predominantly consisted of the austenitic (γ) phase with a minimal amount of δ-ferrite phases in both stainless steels. The elemental distribution confirmed through EDS and verified by the Schaeffler diagram. SS309 exhibited a higher δ ferrite content compared to SS316L, and the interfaces showed a δ-ferrite content between the two base metals, the δ-ferrite mitigate the issue of hot cracking which occurred generally in the austenitic steels. The hardness ranged from 206 to 289 Vickers hardness (HV), with a considerable increase at the interface due to concentration of δ ferrite. The yield and ultimate tensile strengths were higher in the bimetallic samples tested in the build direction compared to the deposition direction with minimal variation indicating low anisotropy in mechanical properties. Tensile fracture results showed dimples, deep dimples, and microcracks, with failures occurring on the SS316L side. These findings demonstrate the effectiveness of the wire arc DED process in fabricating of bimetallic structure of SS316L-SS309 with improved strength.